The Role of Teaching Aids in The Effective Teaching of English Language in Preparatory Schools - Fatma Jawad Boubakar (Journal of Scientific and Human Dimensions, 2026)
This study investigates the role of teaching aids in enhancing the teaching and learning of the English language in preparatory schools in Libya, with a focus on schools in the cities of Al Qubba and Ain Mara. Despite the recognized importance of instructional materials in promoting language development, many classrooms still lack the effective use of teaching aids due to limited awareness, training, and resources. The study employed a mixed-methods research design, combining quantitative data from questionnaires and qualitative insights from teacher interviews. A total of 50 English language teachers participated in the research. Findings revealed that most teachers believe teaching aids positively impact student performance, increase engagement, and simplify complex concepts. However, challenges such as lack of resources, insufficient training, and large class sizes often limit their use. The study concludes that teaching aids are essential tools for modern language instruction and recommends investing in teacher training, providing diverse instructional materials, and developing supportive educational policies. This research contributes valuable insight into the practical use of teaching aids and offers a path forward for improving English language education in Libyan preparatory schools.